Effects of Oxidation Curing of Polycarbosilane on Dielectric and Microwave Absorption Properties of PDCs‐SiC Ceramics. Issue 1 (15th June 2015) - Shi, Yimin; Luo, Fa; Ding, Donghai; Wan, Feng; Zhou, Wancheng; Zhu, Dongmei
Abstract : Polycarbosilane (PCS) was cured by oxidizing at different temperatures and pyrolyzed at 1000°C in vacuum. The dielectric properties of SiC ceramics were studied in X band. The ε′ and ε″ of SiC ceramics derived from oxidation‐curing PCS decreased to 4 and 0.35, respectively, which attribute to the decrease of free carbon content and order. SiC ceramic derived from PCS cured at 180°C showed that reflection loss was lower than −10 dB in the frequency range from 8.2 to 11.3 GHz and the minimum value was −26.7 dB at 9.6 GHz, which exhibits a promising prospect as microwave‐absorbing materials.